Karakteristik Fisikokimia dan Penerimaan Konsumen Bakso Ikan Layang (Decapterus sp.) dengan Penambahan Kepala Tulang Ikan Lumat (KTIL) - Febrianti, Aulia; Pamungkas, Bagus Fajar; Irawan, Irman; Asikin, Andi Noor; Diachanty, Seftylia (Universitas Halu Oleo, 2023)
Decapterus sp is a source of animal protein which is very important for human needs. The potential for the development of the flying fish processing industry will lead to an increase production and the resulting by-products are fish heads and bones, which still have the potential to be reused. One of its uses is by applying it to the manufacture of fish balls. The addition of various additives will result in different chemical characteristics and consumer acceptance. This study purpose to determine the physicochemical characteristics and consumer acceptance of flying fish meatballs (Decapterus sp) added head and crushed fish bones (KTIL). This study used a completely randomized design (CRD) with four treatments and three replications, namely P0(fish meat 25g), P1(fish meat 237.5g: KTIL 12.5g), P2(fish meat 225g : KTIL 25g), P3 (fish meat 212.5g : KTIL 37.5g). The statistical analysis used was analysis of variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at the 95% confidence level. Parameters observed included chemistry (moisture content, ash, fat, protein), color, EMC and consumer acceptance. The results of research with the addition of KTIL in the manufacture of flying fish balls produced physicochemical characteristics such as water content 64.51% -67.49%, ash 1.56% -2.25%, protein 16.67% -18.54%, fat content 1.53%-1.95 %, L* value 51.66-55.47, a* value 0.01-1.05, b* value 11.53-12.50, degree of whiteness 54.72-57 .43., and EMC 1.83% -3.31% as well as hedonic tests with taste parameters, aroma ranging from 7.0 (like) - 8.0 (very like), texture ranging from 6.4 (rather like)–8 .0 (like very much) and an overall range of 7.0 (like)–8.0 (like very much).